2016
DOI: 10.1089/dna.2016.3404
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Zika Virus Infection and Neuropathogenesis

Abstract: A spotlight has been focused on the mosquito-borne Zika virus (ZIKV) because of its epidemic outbreak in Brazil and Latin America, as well as the severe neurological manifestations of microcephaly and Guillain-Barré syndrome associated with infection. In this review, we discuss the recent literature on ZIKV-host interactions, including new mechanistic insight concerning the basis of ZIKV-induced neuropathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
50
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 48 publications
0
50
0
1
Order By: Relevance
“…The numbers of people infected in these outbreaks were unprecedentedly high. More severe complications, including birth defects and neurological disorders, were observed (5,6). New modes of transmission, including blood-borne, transplacental, and sexual transmission, were also found (1,7).…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…The numbers of people infected in these outbreaks were unprecedentedly high. More severe complications, including birth defects and neurological disorders, were observed (5,6). New modes of transmission, including blood-borne, transplacental, and sexual transmission, were also found (1,7).…”
mentioning
confidence: 92%
“…Although it remains to be determined whether mutations have enabled ZIKV to become more pathogenic and transmissible (19), innate immunity is thought to govern both viral replication and pathogenesis (6,20). Indeed, innate antiviral effectors, such as type I and type III interferons (IFNs), are capable of suppressing ZIKV replication (21,22).…”
mentioning
confidence: 99%
“…Olagnier et al [72] have suggested that the viral infection of fetal neural progenitor cells could activate TLR3 immune responses, leading to a deregulation of genes that control apoptosis, resulting in severe damage to the embryonic brain. All of these inflammatory issues are relevant when it comes to a viral infection since the immune system may respond differently.…”
Section: Neuroimmunomodulation Of Asd and Zikvmentioning
confidence: 99%
“…The transplacental transmission of Zika virus from mother to foetus may occur by the infection of placental macrophages (Hofbauer cells) and cytotrophoblasts [59]. Macrophages are the main target cells of Zika viral infection in the placenta [60]. Viral infection in placental macrophages induces the production of type I interferon and pro-inflammatory cytokines resulting in an antiviral gene expression [60].…”
Section: Possible Molecular Events Leading To Microcephalymentioning
confidence: 99%
“…Macrophages are the main target cells of Zika viral infection in the placenta [60]. Viral infection in placental macrophages induces the production of type I interferon and pro-inflammatory cytokines resulting in an antiviral gene expression [60]. …”
Section: Possible Molecular Events Leading To Microcephalymentioning
confidence: 99%